Survey of farm management and biosecurity practices on shrimp farms on Java Island, Indonesia - Patanasatienkul, Thitiwan; Gautam, Milan; Hammell, K. Larry; Gilang, Dimas; Delphino, Marina K. V. C.; Burnley, Holly; Salsabila, Nikmatun Aliyah; Thakur, Krishna K. (Frontiers in Aquaculture, 2023)
Current information on biosecurity measures implemented by shrimp farmers in Indonesia is limited. This study describes farmer demographic characteristics, on-farm biosecurity practices, farm production and disease status, among small and medium holder shrimp farms on Java Island, Indonesia. A questionnaire-based survey was conducted from November 2019 to May 2020 to collect data from shrimp farms operating in various regions of the Java Island. A numerical score was assigned for each of the assessed biosecurity practices, based on whether it was a conventional risk factor or a protective factor. Based on responses from 90 shrimp farmers, who volunteered to participate in the study, mean overall biosecurity scores ranged from 32 to 54 (out of a maximum score of 100). Most farms (88.9%) either shared common water sources with other aquaculture farms or were connected to other farms via water channel. Farm equipment sharing was common both within (91.1%) and between (41%) farms. Water pre-treatment was common (99%), but approximately a third of the farms did not practice any routine quality assessment for post larvae before stocking. On average, farms produced 1.6 kg/m2 (95% CI: 1.2, 2.0) of shrimp with a harvest size of 43 shrimp/kg (95% CI: 37, 49) or an average weight of 23.3 g at time of harvest. An increasing trend in harvest weight per pond area and shrimp size at harvest was noted with increasing overall biosecurity score. These results indicated that farms with better biosecurity practices tended to have a higher production yield.